Analysis of Stator Ventilation Channel Steel Structures to Improve Heat Dissipation Performance of Medium-sized High Voltage Motors - Deqi PENG; Hang ZENG; Wei YIN; Xiaohui ZHOU; Guang LI; Run AI; Zhuowei TAN (工程科学与技术)
In order to reduce the ventilation and heat dissipation performance of the YJK450–6, 400 kW medium-sized high-voltage motors, the heat dissipation performance of different ventilation channel steel structures of these motors was studied in this paper. Firstly, on the basis of the linear standard ventilation structure of the existing motor, three axial–radial hybrid ventilation structure forms were proposed, those are the single-row scaling type, the double-row linear type and the double-row scaling type. The 3D numerical calculation model of the temperature field of the motor was established in the SpaceClaim software. The simulation parameters of the motor were calculated according to the basic assumptions, the boundary conditions and the internal heat transfer formula of the motor. The simulation was carried out by Fluent software. Notably, the heat source for calculating the temperature field was obtained by the motor loss value computed by the Ansoft Maxwell platform. Secondly, the 3D numerical calculation model of the temperature field established in this paper was validated through the grid independence and temperature rise tests. A comparative analysis was conducted through simulation to assess the impact of the three axial–radial hybrid ventilation structures and the linear standard structure. The orthogonal test method was used to optimize the parameters of the axial–radial mixed ventilation structure to obtain the optimal heat dissipation structure and parameter scheme. The effect of cooling air velocity on the heat transfer performance of the double-row scaled channel steel was further explored. Combined with the temperature rise of the stator windings and the uniformity coefficient of the overall temperature rise of the motor, the heat dissipation effect of the optimal heat dissipation structure and parameter scheme of the motor was evaluated. The simulation results showed that the calculation model established in this paper is effective. The double-row scaling ventilation channel steel structure exhibit the best heat dissipation performance indexes, making it the optimal ventilation channel steel structure. The double-row scaling ventilation channel steel structure with a radial air duct height of 6 mm and a quantity of 13 is identified as the optimal heat dissipation structure and parameter scheme. The average convective heat transfer coefficient on both sides of the double-row scaling ventilation channel steel structure increases with the cooling air velocity, and the average convective heat transfer coefficient on the windward side of the channel steel is significantly higher than that on the leeward side. Compared to that of the linear standard motor, the uniformity coefficient of temperature rise distribution of the inner/outer windings of the double-row scaling ventilation channel steel structure motor with a radial duct height of 6 mm and a quantity of 13 increase by 88.13% and 20.11% respectively. Therefore, the optimal design of the ventilation channel steel structure is conducive to the internal air flow and heat dissipation of the motor, which can effectively reduce the internal temperature rise of the motor.